Alterações no periodonto de proteção e ligamento periodontal em molares de ratos submetidos ao etanol durante a lactação: estudo histopatológico e histométrico - Curi, Viviane (2010)
Alcoholism is a public health problem worldwide, involving thousands of men and women, bringing serious consequences as a disease in all organs of the human body, especially the stomach, liver, heart and brain. The consumption of alcoholic beverages for infants and mothers have attracted the attention of researchers in recent decades, with significant. Objective: This study aimed to evaluate the effects of ethanol in the junctional epithelium, adamantine epithelium, epithelium of attached gingiva and periodontal ligament of the upper first molar of the rat, during lactation. Materials and Methods: To this end, we used mice with a day of postnatal life, whose mothers received 20% ethanol in drinking water and rats whose mothers do not received ethanol during the entire lactation. After 21 days, the chicks were sacrificed with anesthetic overdose (Hypnol 3%). The heads were separated and fixed in a solution of "alfac" (alcohol 80% -85 ml, 10 ml of formalin and acetic acid 5-ml), embedded in paraffin and frontal serial sections were stained with hematoxylin and eosin. The cuts were focused light microscope (100x) fitted with a camera lucida. The nuclei of cells from tissue fragments were designed on paper with increased end of 1000x. and 50 nuclei of each structure were outlined with black pencil for later measurement of larger (D) and smaller (d)diameters. Once determined the diameters were estimated karyometric following parameters: geometric mean diameter ratio D / d, perimeter, area, volume, relationship between volume and area, eccentricity, shape coefficient and contour índex. This work also was done using a grid printed on paper. The images were drawn on the grid. In order to assess the volumes and cell cytoplasm, the nucleus / xxiv cytoplasm ratio, the numerical cell density, relation to the external surface / basal layer, the thickness of epithelial layers and the density of the surface was sometimes used the count of the points and sometimes the number of intersections and applied to stereological equations appropriate for each of these variables. All data collected were submitted to non-parametric statistics (Wilcoxon-Mann-Whitney). Results: Histologically, the superior maxillar molar tooth of the rat treated with ethanol was not erupted or partially eruído; the junctional epithelium was reduced and the adamant epithelium was in full function and consists of high palisade cells. The epithelium of attached gingiva was more slender and composed of smaller cells. In the Periodontal ligament was possible to observe bigger and disorganizedfibers. The nuclei of the epithelia studies have shown decreased values after Karyometry, for larger and smaller medium diameters, volume, area, perimeter, and the relation V / A. Stereologically could be observed in the junctional epithelium, adamantine and the attached gingiva, less voluminous cell with scarce cytoplasm leading to a greater number of cells per mm3 of tissue. The disorganized periodontal ligament showed larger fibers with smaller number per mm3. Conclusion: In this study, ethanol resulted in a framework of epithelial hypotrophy, indicating a direct action on the junctional and adamantineepithelium, epithelium of attached gingiva and periodontal ligament.